Detection of Giardia lamblia in children by microscopy, ELISA and real time PCR assay (Dhaka University Journal of Biological Sciences, 2014)
Conventional microscopy, ELISA and Real Time PCR showed Giardia lamblia in a total of 4470 asymptomatic and 423 symptomatic faecal samples from urban slum children of 13 ? 60 months age old. ELISA showed more sensitivity (88.88%) and specificity (90.91%) than microscopy (6.5% sensitive and 100% specific). The prevalence of G. lamblia infection among asymptomatic children was 37.93% by microscopy and 76.11% by ELISA. The prevalence was 7.03, 38.91 and 66.49 by microscopy, ELISA and Real Time PCR in symptomatic children, respectively. The highest prevalence (80.95%) of infection was found in symptomatic children between 49 and 60 months old. Peak prevalence among asymptomatic children was found in March, 2012 (39.39%) and among symptomatic children in September, 2012 (88.88%). Giardia lamblia infection was higher (71.03%) in male than in female children (60.26%). DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20100 Dhaka Univ. J. Biol. Sci. 23(2): 197-204, 2014